Deep inspiration breath‐hold technique guided by an opto‐electronic system for extracranial stereotactic treatments. (8th July 2013) - Garibaldi, Cristina; Catalano, Gianpiero; Baroni, Guido; Tagaste, Barbara; Riboldi, Marco; Spadea, Maria Francesca; Ciocca, Mario; Cambria, Raffaella; Serafini, Flavia; Orecchia, Roberto
Abstract : The purpose of this work was to evaluate the intrapatient tumor position reproducibility in a deep inspiration breath‐hold (DIBH) technique based on two infrared optical tracking systems, ExacTrac and ELITETM, in stereotactic treatment of lung and liver lesions. After a feasibility study, the technique was applied to 15 patients. Each patient, provided with a real‐time visual feedback of external optical marker displacements, underwent a full DIBH, a free‐breathing (FB), and three consecutive DIBH CT‐scans centered on the lesion to evaluate the tumor position reproducibility. The mean reproducibility of tumor position during repeated DIBH was 0.5 ± 0.3 mm in laterolateral (LL), 1.0 ± 0.9 mm in anteroposterior (AP), and 1.4 ± 0.9 mm in craniocaudal (CC) direction for lung lesions, and 1.0 ± 0.6 mm in LL, 1.1 ± 0.5 mm in AP, and 1.2 ± 0.4 mm in CC direction for liver lesions. Intra‐and interbreath‐hold reproducibility during treatment, as determined by optical markers displacements, was below 1 mm and 3 mm, respectively, in all directions for all patients. Optically‐guided DIBH technique provides a simple noninvasive method to minimize breathing motion for collaborative patients. For each patient, it is important to ensure that the tumor position is reproducible with respect to the external markers configuration. PACS numbers: 87.53.Ly, 87.55.km